2012
DOI: 10.1093/nar/gks502
|View full text |Cite
|
Sign up to set email alerts
|

Engineering domain fusion chimeras from I-OnuI family LAGLIDADG homing endonucleases

Abstract: Although engineered LAGLIDADG homing endonucleases (LHEs) are finding increasing applications in biotechnology, their generation remains a challenging, industrial-scale process. As new single-chain LAGLIDADG nuclease scaffolds are identified, however, an alternative paradigm is emerging: identification of an LHE scaffold whose native cleavage site is a close match to a desired target sequence, followed by small-scale engineering to modestly refine recognition specificity. The application of this paradigm could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…A common strategy for engineering LHEs with altered specificity is to fuse two halves (or domains) from different LHEs, each with different DNA-binding specificity (14,16,(35)(36)(37)(38). This strategy has been successful, particularly when the N-and C-terminal domains are derived from closely related LHEs.…”
Section: Suppressor Mutations In the Coevolving Network Can Rescue Sumentioning
confidence: 99%
See 1 more Smart Citation
“…A common strategy for engineering LHEs with altered specificity is to fuse two halves (or domains) from different LHEs, each with different DNA-binding specificity (14,16,(35)(36)(37)(38). This strategy has been successful, particularly when the N-and C-terminal domains are derived from closely related LHEs.…”
Section: Suppressor Mutations In the Coevolving Network Can Rescue Sumentioning
confidence: 99%
“…Moreover, the monomeric and dimeric LHEs likely evolved under different functional constraints, and the phylogenetic signal and functional information for either form is diluted in alignments that include both the monomeric and dimeric LHEs. Because LHEs are currently under investigation for use as genome-editing agents (16)(17)(18), a greater understanding of their functional constraints would aid in engineering studies.…”
mentioning
confidence: 99%
“…In our experience, up to 50 % of I-OnuI family chimeras show significant cleavage activity with this direct domain fusion method [4]. However, certain enzyme combinations will be incompatible and require further engineering to achieve DNA cleavage activity.…”
Section: Methodsmentioning
confidence: 99%
“…The structural dissimilarity of these two parent enzymes made necessary both computational modeling and in vitro selection to repack the chimeric interface. Based on this work, it was hypothesized and confirmed that the generation of chimeras from within a family of highly homologous monomeric LHEs could produce a large number of active enzymes with minimal engineering [4]. …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation